2013
DOI: 10.1371/journal.pone.0059602
|View full text |Cite
|
Sign up to set email alerts
|

T Cells Contribute to Stroke-Induced Lymphopenia in Rats

Abstract: Stroke-induced immunodepression (SIID) results when T cell and non-T immune cells, such as B cells, NK cells and monocytes, are reduced in the peripheral blood and spleen after stroke. We investigated the hypothesis that T cells are required for the reductions in non-T cell subsets observed in SIID, and further examined a potential correlation between lymphopenia and High-mobility group protein B1 (HMGB1) release, a protein that regulates inflammation and immunodepression. Our results showed that focal ischemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
35
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 50 publications
1
35
0
Order By: Relevance
“…T cells, Tregs, NK cells, B cells and monocytes 72 h after stroke, accompanied by a significant reduction in spleen weight [32]. Finally, we observed that dMCAO induced significant inhibition of the proliferative ability of splenocytes stimulated by T cell mitogen Concanavalin A [32]. These results serve to confirm that stroke induces lymphopenia,-likely contributing to an inhibition of immune function.…”
Section: T Cells Contribute To Stroke-induced Lymphopenia Stroke Indusupporting
confidence: 70%
See 4 more Smart Citations
“…T cells, Tregs, NK cells, B cells and monocytes 72 h after stroke, accompanied by a significant reduction in spleen weight [32]. Finally, we observed that dMCAO induced significant inhibition of the proliferative ability of splenocytes stimulated by T cell mitogen Concanavalin A [32]. These results serve to confirm that stroke induces lymphopenia,-likely contributing to an inhibition of immune function.…”
Section: T Cells Contribute To Stroke-induced Lymphopenia Stroke Indusupporting
confidence: 70%
“…Earlier studies in experimental models of cerebral ischemia demonstrated that T cells were recruited and involved in the ischemic brain at later stages (3 days post-ischemia) [27][28][29] compared with the significantly increased infiltration of activated microglia/macrophages and neutrophils at earlier times (several minutes to hours post-ischemia) [29]. More recent studies including our results showed that within the first 24 h, T cells and their subsets were involved or recruited in the ischemic brain after focal ischemia in experimental animal models [5,7,24,[30][31][32][33]. Yilmaz et al [5] reported that CD4 ?…”
Section: T Cells Are Involved In Brain Injury After Cerebral Ischemiamentioning
confidence: 49%
See 3 more Smart Citations